Die internationale Stadt Tanger Infrastrukturen des geteilten Kolonialismus, 1840-1956 - Hettstedt, Daniela (Studien zur Internationalen Geschichte, 2022)
The international history of the city of Tangier begins long before its time as a specific administrative zone. As early as 1840, the city became the seat of important commissions that controlled access to the Strait of Gibraltar on behalf of infrastructure projects and shaped the cityscape. Daniela Hettstedt examines the intertwining of international and colonial mechanisms of rule as "shared colonialism" in its local consequences.